De-policing queer possibilities - Rangel, Michael (2020)
In the wake of a policed dystopia that is decreed by both state and social formations, this project develops an understanding of the performance and engagements of policing on racialized queer subjects. Through case and textual analysis, this project examines Black and Brown subjectivities that do the work of imagination, survival, and resistance that contest their possibilities of living. Bringing together Queer theorist and Black Feminist perspectives to define Queer subjectivity, possibility, and the tactical performance of policing- this project creates a theoretical framework about how de-policing Queer and racialized subjectivity and performance can be a life saving strategy that centers the possibilities of life over death. This project develops a new understanding of how de-policing occurs within the contemporary conditions of spatial, legal, material, and geographical dimensions of queerness and raciality. De-Policing Queer Possibilities is set to articulate a robust understanding of the police state, racialized queer and trans realities, and possibility-making in both a transnational and contemporary U.S. framework